Spatial Patterns and Determinants of the Diversity of Hemipteran Insects in the Qinghai-Tibetan Plateau - Li, Junjie; Liu, Huanhuan; Wu, Yangxue; Zeng, Lingda; Huang, Xiaolei (Frontiers in Ecology and Evolution, 2019)
Large-scale patterns of species richness is an important issue in biogeography and ecology. The Qinghai-Tibetan Plateau (QTP) is a biodiversity hotspot in the world, which has an important status in the zoogeographical realms. Here, we analyzed the diversity patterns of Hemipteran insects in the QTP, and tested whether the patterns can be jointly explained by modern environmental as well as historical factors. A comprehensive geographic distribution dataset consisting of 1166 Hemipteran species, which belong to 510 genera and 53 families, was compiled and used in our analyses. Patterns of richness were mapped into a grid-based map with a spatial resolution of 0.5°x 0.5°. An unbalanced diversity pattern of the Hemipteran insects in the QTP was presented, with more species in the eastern and southern parts of the plateau, while few species in the northern and main surface of the plateau. The northwestern Sichuan, the southern Gansu, the southeastern Tibet, the northwestern Yunnan and the eastern Qinghai were identified as diversity hotspots of species richness. Further analyses based on General linear models and Random Forest indicated that the diversity patterns of Hemipteran insects were influenced by both contemporary environmental factors and historical factors (e.g. habitat heterogeneity, climate stability, energy availability). Specifically, the species richness patterns of all Hemipteran insects in the QTP have been mainly affected by elevation range, temperature annual range, min temperature of coldest month, mean temperature of coldest quarter and the temperature change since the Last Glacial Maximum. In contrast, the water-related variables have relatively small effects on species richness. In addition, although habitat heterogeneity was indicated the most important factor for different suborders of Hemiptera, the climate stability was another dominate factor for Heteroptera and Auchenorrhyncha, while Sternorrhyncha was more affected by historical climate change.